Biosynthesis of zinc oxide microparticles by using palm oil leaves extract - Adnan A. Alshaer, Adnan A. Alshaer; Ainun Rahmahwati, Ainun Rahmahwati; Ramzi Qasem, Ramzi Qasem (2021)
Green biosynthesis is a good alternative where plants are used to assist microparticle synthesis which has ecofriendly benefits compared to chemical and physical methods. The aim of this study was to synthesize and characterize zinc oxide microparticles by using palm oil leaves. Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction analysis (XRD) and Field Emission Scanning Electron Microscope (FESEM) were used to characterize the biosynthesized Zinc Oxide microparticles. XRD results revealed the formation of hexagonal wurtzite structure. FT-IR analysis confirmed the formation of chemical bonds in zinc oxide. Finally, (FESEM) analysis showed that the average size of zinc oxide microparticles 0.58 and 0.83 and 1.44 μm at different annealing temperatures of 30, 60 and 90 °C respectively